The relationships between plants and the soils on which they grow - Harper, Peter C. (The University of Edinburgh, 1958)
SECTION I:

The ecological work dealing with the soils and vegetation of regions similar to the eastern Lammermuir Hills has been studied and is reviewed in Chapter I.

The environment and history of the eastern Lammermuir Hills is described in Chapter II.

The soils present in the area have been classi- fied into eight mature types and three skeletal types. They are described in Chapter III and their distributions on the land shown in a coloured map.

Sixteen plant communities have been recognised. These are described in Chapter IV and their spatial distribution shown on a coloured map.

While it is recognised that altitude, aspect and exposure together limit the distribution of cultivation on suitable land it is suggested that the apparent correlation between soil types and vegetation and altitude is due to topography. Only one vegetation type shows an association with a particular aspect and it is present in few places. Exposure cannot be separated from topography in a study of this type.

The soil types form a natural hydrologic sequence controlled by the topography on which they were formed. There is also a correlation between vegetation and topography which, it is suggested, is indirect.

There is a strong association between particular soil types and particular vegetation types.

SECTION II.

1. The methods used in conducting the survey are described.

2. In Chapter VIII, material is presented which confirms the findings of Section 1, that each plant community is associated with a particular soil type or group of soil types.

3. The values of acidity, loss on ignition, and depth of topsoil are given for each plant community.

4. The species content of the flora in relation to soil factors is examined. It is found that podzols are poorest and non -calcareous gleys richest in this respect. Neutral and mineral soils bear more species than acid or organic soils respectively.

5. Evidence is presented which shows the relationships of the distribution of each of fifty-four species in relation to soil type and three soil factors.

6. The discussion deals with some general points not touched upon in the accounts of the various species and puts forward the suggestion that soil-plant relationships may form one basis of a floristic classification of plant communities.